Anticarcinogenic afficacy of phytic acid extracted from rice bran on azoxymethane-induced colon carcinogenesis in rats - Saad, Norazalina; Mohd Esa, Norhaizan; Ithnin, Hairuszah; Mohamed Shakirin, Norashareena (Elsevier, 2010)
This study is carried out to determine the potential of phytic acid extracted from rice bran in the suppression of colon carcinogenesis induced by azoxymethane (AOM) in rats. Seventy-two male Sprague-Dawley rats were divided into 6 groups with 12 rats in each group. The intended rats for cancer treatment received two intraperitoneal injections of AOM in saline (15mg/kg bodyweight) over a 2-week period. The treatments of phytic acid were given in two concentrations: 0.2% (w/v) and 0.5% (w/v) during the post-initiation phase of carcinogenesis phase via drinking water. The colons of the animals were analyzed for detection and quantification of aberrant crypt foci (ACF) after 8 weeks of treatment. The finding showed treatment with 0.2% (w/v) extract phytic acid (EPA) gave the greatest reduction in the formation of ACF. In addition, phytic acid significantly suppressed the number of ACF in the distal, middle and proximal colon as compared to AOM alone (p<0.05). For the histological classification of ACF, treatment with 0.5% (w/v) commercial phytic acid (CPA) had the highest percentage (71%) of non-dysplastic ACF followed by treatment with 0.2% (w/v) EPA (61%). Administration of phytic acid also reduced the incidence and multiplicity of total tumors even though there were no significant differences between groups. In conclusion, this study found the potential value of phytic acid extracted from rice bran in reducing colon cancer risk in rats.